Attitudes toward doping among Polish athletes measured with the Polish version of Petroczi`s Performance Enhancement Attitude Scale - Sas-Nowosielski, K.; Budzisz, A. (Polish Journal of Sport and Tourism, 2018)
Introduction. The aim of the study was twofold. The first aim was to specify attitudes toward using performance-enhancing drugs (doping) among athletes practising different sports disciplines. The second aim was to present the Polish version and validation of the Performance Enhancement Attitude Scale (PEAS). Material and methods. A total of 340 athletes (173 males and 167 females) took part in the study. They represented 13 sport disciplines. The study was conducted in Central Sports Centres in Poland. Athletes` attitudes were assessed using the Performance Enhancement Attitude Scale (PEAS). Results. The study revealed that athletes generally were not tolerant in relation to illegal performance-enhancing substances in sport. However, men were more permissive toward illegal performance enhancement than women. The other important factor, apart from gender, was the amount of contact between competitors. The lowest values were found for sports where athletes competed parallel to each other, medium values were recorded for sports where athletes were in close contact, and the highest values were found in the group of athletes having no contact with the competitors. Our analyses also confirmed that the 11-item version of PEAS has the best fit indices and therefore is most recommended for use among Polish athletes. Conclusions. The Polish version of PEAS is recommended in its 11-item version, and its reliability was confirmed. According to the findings of the study, Polish athletes rather do not approve of doping behaviours. Men were more likely to use illegal substances than women. The most positive attitude towards doping was found for sport disciplines where there is no contact with the competitor.